2012
DOI: 10.1097/dad.0b013e31825aa415
|View full text |Cite
|
Sign up to set email alerts
|

Granular Cell Variant of Epithelioid Cell Histiocytoma

Abstract: Classic granular cell tumors (GCTs) stain strongly and uniformly positive for S100 protein and are believed to show Schwann cell derivation. Polypoid cutaneous tumors composed of cells with large nuclei and abundant granular cytoplasm that do not stain for S100 protein or show apparent Schwannian differentiation have been reported by several groups under names including "primitive polypoid granular cell tumors," "dermal nonneural granular cell tumor," and "primitive nonneural granular cell tumors of skin." We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Interestingly, the resemblance between NN-GCT and the granular cell variant of EFH has been previously noted. 4,5 The presence of well-circumscribed borders, epidermal collarettes, a low mitotic rate and mild/no atypia are features shared between our cases and these isolated reports, hinting at their diagnosis. It is, however, worth mentioning that, in the largest series of NN-GCTs, these aspects were not ubiquitously present, indicating the heterogeneity of this category of tumours and that our findings may not be extrapolated to all cases.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Interestingly, the resemblance between NN-GCT and the granular cell variant of EFH has been previously noted. 4,5 The presence of well-circumscribed borders, epidermal collarettes, a low mitotic rate and mild/no atypia are features shared between our cases and these isolated reports, hinting at their diagnosis. It is, however, worth mentioning that, in the largest series of NN-GCTs, these aspects were not ubiquitously present, indicating the heterogeneity of this category of tumours and that our findings may not be extrapolated to all cases.…”
supporting
confidence: 64%
“…Following these efforts, two isolated case reports suggested that NN-GCT might correspond to a granular cell variant of epithelioid fibrous histiocytoma (EFH). 4,5 However, these statements were mostly based on morphological features, without the support of more specific ancillary techniques.…”
mentioning
confidence: 99%
“…These histological findings simulate those of Spitz's nevi and, to a lesser degree, pyogenic granuloma, reticulohistiocytoma, atypical fibrous histiocytoma, epithelioid hemangioma, neurothekeoma, cutaneous rhabdoid tumor, non‐lipidized xanthogranuloma and epithelioid sarcoma . ECH is S100 protein negative, and stains positively with factor XIIIa and CD68 . These tumors can also fit the profile of NN‐GCT …”
Section: Tumors That Can Exhibit Granular Cell Changementioning
confidence: 59%
“…38 ECH is S100 protein negative, and stains positively with factor XIIIa and CD68. 39 These tumors can also fit the profile of NN-GCT. 39…”
Section: Dermal Non-neural Gctmentioning
confidence: 99%
“…There are numerous histologic variants of FH with unique microscopic and immunohistochemical features [38]. Cases of common FH and variants exhibiting granular cell change have been described on the skin [39][40][41][42][43][44], as well as in the oral cavity [19]. The histologic features of a common FH are described as a mixture of fibroblastic and histiocytic cells in a storiform pattern with collagen trapping [19], and typically a grenz zone is present beneath the overlying epidermis [38].…”
Section: Discussionmentioning
confidence: 99%